Architecture In-Play, future challenges - Paio, A.; Osório, F. C.; Oliveira, S. M.; Valenti, Graziano Mario; Guimarães, N. (Nexus Network Journal, 2018)
This paper discusses an emerging field of research in architecture. Kinetic design has been used through history, but the speed and technological advances of the 3rd Industrial revolution offers new perspectives and design innovation. To face this demand architects must create new strategies rooted in performance, connectivity and control, and process them toward to inform the design. In order to explore these challenges a group of researchers organized a summer school in 2016. The partnership between ISCTE-IUL and La Sapienza University of Rome emerged as a great opportunity to join an international community to present the most recent works in research, teaching or practice related to architecture, technology, computation, mathematics and geometry. In addition, was developed a learning-by-doing experimental design studio which allowed testing a digital workflow to create a foldable surfaces based on rigid origami geometry. The major objective was contributing to enrich the debate around digitally-driven kinetic architecture.